2019
DOI: 10.18502/ijps.v14i2.992
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acceptance and Commitment Therapy in Reducing Disappointment, Psychological Distress, and Psychasthenia among Systemic lupus Erythematosus (SLE) Patients

Abstract: Objective: The aim of this study was to evaluate the efficacy of acceptance and commitment therapy (ACT) in the reduction of disappointment, psychological distress, and psychasthenia among patients with systemic lupus erythematosus (SLE). Method: This quasi-experimental study was conducted on 24 females with lupus who referred to the Rheumatoid Disease Research Center (RDRC) of Ghaem hospital in Mashhad, Iran. This study had a pretest-posttest control group design. The participants were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In two studies by Behrouz et al 29 and Amsberg et al, 40 the use of ACT was effective on the reduction of the symptoms of depression, anxiety and stress. In addition, ACT impacted hopelessness in the study by Sahebari et al 41 and perceived stress and selfefficacy in the study by Moazzezi et al 42 The commitment to use emotional control, adherence to behavioral commitment, clarification of values and doing behaviors that are consistent with values that accompany expression of metaphors, defusion and acceptance during ACT can be effective in improving diabetes-related emotional distress. In this regard, the patients are helped to accept their thoughts and feelings and be committed to changes in their thoughts or behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…In two studies by Behrouz et al 29 and Amsberg et al, 40 the use of ACT was effective on the reduction of the symptoms of depression, anxiety and stress. In addition, ACT impacted hopelessness in the study by Sahebari et al 41 and perceived stress and selfefficacy in the study by Moazzezi et al 42 The commitment to use emotional control, adherence to behavioral commitment, clarification of values and doing behaviors that are consistent with values that accompany expression of metaphors, defusion and acceptance during ACT can be effective in improving diabetes-related emotional distress. In this regard, the patients are helped to accept their thoughts and feelings and be committed to changes in their thoughts or behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…Eleven additional studies (48%) tested face-to-face interventions. Studies that tested face-to-face interventions were either delivered in a hospital, 23,25,34,37 clinic, 28,30,31,39 or unspecified but authors indicated participants “attended sessions.” 26,29,35…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…The majority of studies (57%) were of psychological interventions (n = 12). 22,26,2835,37,40 Eight of the studies (35%) were of physical activity interventions. 20,2325,27,36,41,42 Two of the studies (9%) were of diet-based interventions.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the effectiveness of ACT on depression [28,29]. Performing various methods such as explaining creative disappointment and value clarification technique were effective on improving depression [30][31][32]. Since patients with CD are confused about life and suffer from depression, reminding purpose of life and identifying values can motivate patients.…”
Section: Discussionmentioning
confidence: 99%